Ecophysiology of natural regeneration of forest stands in Spain - Pardos, M.=700 1 Ruiz del Castillo, j.; Cañellas.I.; Moreno, G.
(Es, En)
ilus., 78 ref.
Keywords: REGENERACION NATURAL; SEMILLAS; REBROTE; FACTORES AMBIENTALES; ESPAÑA